OP0234 Rheumatoid Arthritis Subsets Defined by Sub-Specificities of Anti-Citrullinated Antibodies (ACPAS) Have Unique HLA Associations. (15th July 2016) - Brynedal, B.; Terao, C.; Chen, Z.; Jiang, X.; Westerlind, H.; Hansson, M.; Jakobsson, P.-J.; Skriner, K.; Serre, G.; Rönnelid, J.; Padyukov, L.; Gregersen, P.; et al.
Abstract : Background: Antibodies (Ab) towards citrullinated (cit) peptides (ACPA) are specific serological markers for a subset of rheumatoid arthritis (RA) patients with distinct genetic and environmental associations [1, 2]. On the autoantigen-derived peptide level, the ACPA responses in RA patients are heterogeneous. Better understanding of the relationships between immunity to defined peptides, and structural variants of HLA molecules may provide novel insights concerning HLA-driven pathology in RA. Objectives: To investigate whether RA specific Ab towards cit peptides can detect subsets of patients with distinct associations to different HLA structures. Methods: We used a multiplex peptide array [3] to detect reactivities in sera of patients (n=6400) and selected controls (n=12000) across cohorts from Sweden (EIRA), United Kingdom (WTCCC), and the United States (NARAC). Genetic data from the immunochip platform was used to investigate variation in the HLA region. First, we tested the association between AA-alleles of HLA molecules and Ab defined strata of RA patients. In order to quantify the similarity between different peptide reactivities we used permutation, scaled Jaccard distance metrics and hierarchical clustering. Next, we assessed genetic associations with antibody titers in RA cases, and estimated interactive effects on susceptibility to Ab-positive RA. Results: Comparing 20 different ACPAs reactive with different cit peptides, we observed that reactivities to specific peptides are highly correlated across patients (>87% pairs co-occurs more than expected). The majority of Abs are highly co-expressed in patients who have high frequencies of HLA-alleles known to be associated to ACPA-positive RA. AA at positions 11/13 of HLA-DRB1 display the strongest susceptibility to 18 fine-specific ACPAs (omnibus p≤9.3x10 –64 ), the exceptions being reactivities towards cit Fibrinogen (Fib) β 62–81 with citrullination at position 72 or 74. The reactivities towards two Fib peptides are not highly co-occurring with other Ab; The expression of Ab against cit Fib α peptide 36–50 is independent of HLA variants and for Ab towards cit Fib β 62–81 (72) there is even a negative association to HLA-variants previously shown to associate with ACPA-positive RA. Finally, we observed several allelic combinations showing interactive effects on fine specific ACPAs, and not or weakly with CCP2. Conclusions: RA patients often co-express many different RA specific Ab, and the expressions of most of these are associated to HLA variants linked with ACPA-positive RA. However we also identified ACPAs with distinct expression profiles and HLA associations. References: Klareskog L et al. PMID: 18173373 Raychaudhuri S et al. PMID: 22286218 Hansson M et al. PMID: 23025688 Disclosure of Interest: None declared